Expression of Corticosteroid-Binding Globulin CBG in the Human Heart - Schäfer, H. H.; Gebhart, V. M.; Hertel, K.; Jirikowski, G. F. (Hormone and Metabolic Research, 2015)
Glucocorticoids are known to be involved in myocardial regeneration and destruction. Cardiomyocytes are mostly devoid of nuclear glucocorticoid receptors (GRs) and it is generally assumed that effects of adrenal steroids in heart are mediated through the mineralocorticoid receptor (MR). Here we used immunocytochemistry to study localization of corticosteroid binding globulin (CBG) in semithin sections of human cardiac tissue samples. With staining of consecutive sections we examined colocalization with GR and MR immunoreactivities. While GR staining was almost undetectable, a portion of myocytes with MR immunostained nuclei was found. Almost all cardiomyocytes exhibited CBG immunostaining in cytoplasm and on the cell membrane. Most pronounced CBG immunoreactivities were found in Purkinje fibers and in smooth muscle cells of arterial walls. With RT-PCR, we found in homogenates of cardiac tissue detectable levels of CBG encoding mRNA. Our findings indicate that CBG is expressed in human heart. Known cardiac effects of adrenal steroids may in part be mediated through the binding globulin and its putative membrane receptor in addition to nuclear steroid receptors and direct genomic action. Highlights of our study: Human cardiomyocytes express mineralocorticoid receptors, but are mostly free of nuclear glucocorticoid receptors. CBG is expressed in myocardium and in Purkinje fibers. CBG in heart is colocalized with mineralocorticoid receptor. Endothelia and smooth muscle cells of arterial walls show colocalization of CBG and MR.
Keywords: human myocardium; adrenal steroids; mineralocorticoid receptor; stress hormones; corticosteroid binding globulin